Is tuberculosis in children a severe disease? - Windy Rakhmawati; Kodchakon Piasai (Jurnal Keperawatan Padjadjaran, 2023)
Tuberculosis is one of the health issues over the world. However, childhood TB is often less attention and neglected, particularly in the endemic area, due to the negative result of sputum smear and no specific signs and symptoms among children. Children exposed to infectious disease have a high risk of infection and progressing to TB disease. TB disease among children may develop into a severe form of TB, such as TB meningitis or military TB, and cause death. Therefore, case finding or contact screening is needed to prevent undiagnosed and untreated childhood TB. Parents or family and health professional staff should support adherence to preventive therapy for infected children and anti-TB treatment for TB disease.